Marketing Strategy Analysis in Increasing Sales and Product Quality to Improving Sales of Suzuki Motorcycles Indonesia - Suko, Basuki (Dinasti International Journal of Digital Business Management, 2023)
The marketing strategy is very important for companies where the strategy marketing is a way to achieve the goals of a company, because of the potential for sell proposition limited on amount people who know Thing the. Study this aims to analyze marketing strategies in increasing sales of Suzuki motorcycles on Indonesia. The research method is method quantitative with analysis regression. The conclusion is that the marketing strategy (Product, Price, Place and Promotion) partially or jointly have a significant effect on the Increase Sale. It is recommended that PT management Sunindo Gemilang should further optimize the aspects of product, price, place, promotion. This is done so all these aspects have a better effect so that the increase in sales continues increase and are expected to continue to compete with other companies. So that PT management Sunindo Gemilang Indonesia should further optimize increasing sales through aspects of people, physical evidence, and processes, in addition to product aspects, price, place, promotion.